2018
DOI: 10.3390/catal8030095
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten-Based Mesoporous Silicates W-MMM-E as Heterogeneous Catalysts for Liquid-Phase Oxidations with Aqueous H2O2

Abstract: Mesoporous tungsten-silicates, W-MMM-E, have been prepared following evaporation-induced self-assembly methodology and characterized by elemental analysis, XRD, N 2 adsorption, STEM-HAADF (high angle annular dark field in scanning-TEM mode), DRS UV-vis, and Raman techniques. DRS UV-vis showed the presence of two types of tungsten oxo-species in W-MMM-E samples: isolated tetrahedrally and oligomeric octahedrally coordinated ones, with the ratio depending on the content of tungsten in the catalyst. Materials wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 66 publications
(149 reference statements)
0
13
0
Order By: Relevance
“…Two different methodologies were employed for the catalyst synthesis, namely, evaporation-induced self-assembly (EISA) and solventless dry impregnation of an organometallic Zr precursor onto a commercial mesoporous SiO 2 (OM-DI). Previously, the EISA approach was successfully used for insertion of Ti [27], Nb [32], and W [40] into silicate materials while the OM-DI strategy found application in the preparation of solid oxidic catalysts containing Mo [55,56], Ti and Nb [30,57]. Our present work demonstrated that, regardless of the catalyst preparation method, mesoporous Zr-silicates enable fairly good substrate conversions and product selectivity in the oxidation of bulky alkenes and thioethers.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Two different methodologies were employed for the catalyst synthesis, namely, evaporation-induced self-assembly (EISA) and solventless dry impregnation of an organometallic Zr precursor onto a commercial mesoporous SiO 2 (OM-DI). Previously, the EISA approach was successfully used for insertion of Ti [27], Nb [32], and W [40] into silicate materials while the OM-DI strategy found application in the preparation of solid oxidic catalysts containing Mo [55,56], Ti and Nb [30,57]. Our present work demonstrated that, regardless of the catalyst preparation method, mesoporous Zr-silicates enable fairly good substrate conversions and product selectivity in the oxidation of bulky alkenes and thioethers.…”
Section: Introductionmentioning
confidence: 58%
“…However, several research groups demonstrated that Nb-silicates can be more efficient than Ti-ones in the epoxidation of bulky alkenes with H 2 O 2 and, moreover, possess better stability than the latter [28][29][30][31][32][33][34]. Some success has been recorded in the preparation of tungsten-containing silicates and their use in oxidation catalysis; however, partial tungsten leaching under the conditions of liquid-phase oxidation with H 2 O 2 still remains an unresolved problem [35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Maurya et al reported polymer‐anchored tungsten (VI)(Figure and Figure ) as catalyst for the oxidation of styrene using hydrogen peroxide as oxidant . These polymer‐anchored tungsten (VI) catalysts were prepared by reaction of covalently anchored 2‐(2‐pyridyl)benzimidazole (2‐pybmz) and 2‐(3‐pyridyl)benzimidazole (3‐pybmz) to chloromethylated polystyrene crossed‐linked with 5% divinylbenzene, with metal peroxo species, prepared in situ from WO 3 ⋅H 2 O and an excess of 30% H 2 O 2 .…”
Section: Microporous and Mesoporous Materialsmentioning
confidence: 99%
“…Some transition metal containing catalysts, [13][14][15][16] such as H 2 WO 4 @Al-MCM-41, 12 BaFeO 3Àd , 17,18 Ru(OH) x /g-Al 2 O 3 19 and VO@TiO 2 20 have been proved efficient in catalyzing this reaction with H 2 O 2 as oxidant. Among them, tungsten containing catalysts such as tungsten oxide (WO 3 ), WO 3 nanoparticles, 24 tungstic acid, 25 tungstates and supported WO 3 [26][27][28][29][30] have shown the best catalytic performance. 4,[21][22][23] Although effective in catalytic oxidative cleavage of UFAE, tungsten containing catalyst suffers from active center leaching problem, and thus limits its large scale application.…”
Section: Introductionmentioning
confidence: 99%
“…Some transition metal containing catalysts, 13–16 such as H 2 WO 4 @Al-MCM-41, 12 BaFeO 3− δ , 17,18 Ru(OH) x /γ-Al 2 O 3 19 and VO@TiO 2 20 have been proved efficient in catalyzing this reaction with H 2 O 2 as oxidant. Among them, tungsten containing catalysts such as tungsten oxide (WO 3 ), WO 3 nanoparticles, 24 tungstic acid, 25 tungstates and supported WO 3 26–30 have shown the best catalytic performance. 4,21–23 …”
Section: Introductionmentioning
confidence: 99%